Contribution of Entrepreneurship Learning and Business Mentoring Activities to Create Economic Prosperity for People with Disabilities - Sri Nathasya Br Sitepu; Krismi Budi Sienatra; Uki Yonda Asepta; Irantha Hendrika Kenang (Universitas Pendidikan Ganesha, 2026)
People with disabilities have physical or mental limitations. So, it requires the support of a special learning system for people with disabilities. Entrepreneurship learning and business mentoring activities are needed by people with disabilities to achieve economic independence. This study aims to analyze the contribution of entrepreneurship learning and business mentoring activities to economic independence for people with disabilities. People with disabilities can become entrepreneurs to access income independently. The object of the research involved 1 extraordinary schoolteacher, 5 people with disabilities from Pantiasuhan Bahkti Luhur Sidoarjo with physical limitations and 2 consumers. This research is qualitative research that processes information from respondents. Data collection through in-depth interviews and field observations. The data analysis method uses triangulation of sources and drawing conclusions on the capacity of people with disabilities. The results of the study found that people with disabilities managed to create products, sell and earn an income of Rp.1,000,000 after learning entrepreneurship. People with disabilities manage to sell products and earn income. The benefits of business mentoring activities are reflected in the openness of people with disabilities expressing obstacles during production, selling goods and sharing business exhibitions. The results of the study explained that entrepreneurship learning, and business mentoring activities have succeeded in increasing the capacity of people with disabilities to transform into entrepreneurs. This will have a positive impact in the form of economic independence for people with disabilities in Pantiasuhan Bahkti Luhur Sidoarjo.